2022
DOI: 10.7759/cureus.28238
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Status and Diabetic Retinopathy: A Review

Abstract: Substantial evidence highlights the association between physical inactivity and diabetes onset and complications. Little is known regarding the link between physical inactivity and diabetic retinopathy in terms of onset, progression, and severity. This review aims to investigate these associations and understand the underlying mechanisms behind these associations. Decreased sedentary times and the inclusion of more physical activity have been linked to the delayed onset and progression of diabetic retinopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Physical activity (PA) is a critical component of lifestyle intervention in diabetes management. This study agrees with other studies which revealed that total physical activity was decreased in patients with severe to very severe non-proliferative and proliferative diabetic retinopathy (14,15) Adjusting for age cohorts, frequency of exercise and level of education, the odds of those who are not smoking getting nephropathy reduces by 98% compared to smokers (P-0.0001; CI 0.002549-0.145117). Smoking, a well-known and preventable risk factor for many diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Physical activity (PA) is a critical component of lifestyle intervention in diabetes management. This study agrees with other studies which revealed that total physical activity was decreased in patients with severe to very severe non-proliferative and proliferative diabetic retinopathy (14,15) Adjusting for age cohorts, frequency of exercise and level of education, the odds of those who are not smoking getting nephropathy reduces by 98% compared to smokers (P-0.0001; CI 0.002549-0.145117). Smoking, a well-known and preventable risk factor for many diseases.…”
Section: Discussionsupporting
confidence: 92%
“…They also state that the lack of physical activity is a risk factor for DM and related complications (chronic renal disease, retinopathy). Most patients with T1DM develop DR within the first 20 years of disease, while 60% of patients with T2DM already have DR at the time of DM diagnosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are data that support a protective effect of physical activity against DR, with greater evidence in the most severe DR with initial visual deficit [ 87 ].…”
Section: Obesity and Eye Diseasesmentioning
confidence: 99%